Global Film Color : The Monopack Revolution at Midcentury. - Street, Sarah (Rutgers University Press, 2024)
Global Film Color: The Monopack Revolution at Midcentury explores color filmmaking in a variety of countries and regions including India, China, Japan, and Russia, and across Europe and Africa. Most previous accounts of color film have concentrated on early 20th century color processes and Technicolor. Far less is known about the introduction and application of color technologies in the period from the mid-1940s to the 1980s, when photochemical, "monopack" color stocks came to dominate global film markets. As Eastmancolor, Agfacolor, Fujicolor and other film stocks became broadly available and affordable, national film industries increasingly converted to color, transforming the look and feel of global cinema. Covering a broad range of perspectives, the chapters explore themes such as transnational flows, knowledge exchange and transfer, the cyclical and asymmetrical circulation of technology in a global context, as well as the accompanying transformation of color film aesthetics in the postwar decades.